Find the derivative of the function y = (2x + 12)/(1-x)

Using quotient rule, let u = 2x+12 and v = 1-x. Then we differentiate u and v separately, so u' = 2 and v' = -1. The formula for the quotient rule is: (vu' - uv')/v^2. Plugging in our values into this equation we get: vu'= 2-2x, uv' = -2x-12 and v^2 = (1-x)^2. Then vu' - uv' = 2 - 2x - (2x-12) = 2 -2x + 2x +12 = 14. So (vu' - uv')/v^2 = 14/(1-x)^2

Answered by Mahreen J. Maths tutor

2707 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Why can't you divide something by 0?


(C3) Show that 4csc^2(x) - cot^2(x) = k can be expressed as sec^2(x) = (k-1)/(k-4) where k != 4


What is the probability to obtain exactly 2 heads out of 3 tosses of a fair coin?


integrate 1+ln(x) with respect to x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences